ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT (Studi Empiris pada Perusahaan Manufaktur Industri Sektor Barang Konsumsi yang Terdaftar Di Bursa Efek Indonesia tahun 2014-2016) - Lucky Nugroho (Politeknik Negeri Ambon, 2018)
Currently, the government is prioritizing the development of the manufacturing sector to support national development. Based on the quality of the audit becomes very important to make the right decision for the users of financial statements, especially in the manufacturing sector. Furthermore, this study aims to determine the factors affecting audit quality, especially tenure audit factors, the size of the public accounting firm (KAP), and time budget pressure. Data analysis technique used is logistic regression analysis with the sample of 90 research of manufacture industry sector of consumer goods sector listed in BEI during the year 2014-2016. Based on the result of research indicate that KAP size and time budget pressure have no significant effect on audit quality. While audit tenure has a positive and significant impact on audit quality.